POTENTIAL AREAS ANALYSIS FOR DEVELOPMENT OF PRIME COMMODITIES PLANTATION IN THE KOLAKA DISTRICT, SOUTHEAST SULAWESI - Dhian Herdhiansyah, Lilik Sutiarso, Didik Purwadi, Taryono TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
ABSTRACT Potential areas for development of main commodities plantation in Kolaka district have not been utilized. The objectives of this research were to identify the plantation system of six main commodities, i.e. cocoa, cloves, pepper, cashew, coconut and coffee, and to carry out the potential areas analysis for the development of main commodities plantation in the Kolaka district. The methods used were qualitative descriptive, Delphi, and characteristic gaps analyses of the real condition of the potential areas with the ideal requirements. Potential areas for the development of main potential commodities plantation was cocoa. Cocoa has been a great potential which reachs area of 92,442.24 ha, the production of 309,214.44 tones with a productivity of 558,09 kg/ha, the farmers number of 44,280 families (KK) with average land holdings of 2.14 ha/KK. Gap analysis of the suitability of land for six main commodities i.e. cocoa, cloves, pepper, cashew, coconut and coffee were in the group S (appropriate). The area of potential for the development of cocoa was around of ​​62,708.50 ha, which the largest area was in the Lambadia sub-district of ​​31,638.50 ha with the potential land to be developed land of 2,771 ha and area in the Ladongi sub-district of ​​14,819.40 ha with the potential to be developed of ​​22,900 ha. Keywords: Kolaka district, potential areas, main commodity, plantation